Silver Spot Plating Technique. - Siah, C.H.; Aziz, N.; Samad, Z; Idris, M. N.; Miskam, M.A. (2005)
Electroplating play an important roles in semiconductor manufacturing industries. A layer of silver or gold was selectively plated on the surface of lead frame by using electroplating technology. The purpose of depositing a layer of gold or silver on the surface of lead frame is to improve the bondability during die attach and wire bonding process.